2019
DOI: 10.24135/pjr.v25i1.404
|View full text |Cite
|
Sign up to set email alerts
|

The dichotomy of China Global Television Network’s news coverage

Abstract: Although much is made of the universalisation of ‘US-style’ journalism around the world and Chinese journalists’ shared professional values with counterparts in liberal-democratic countries (Zhang, 2009), the effect of these trends on journalism in China is yet to be fully explored. Using the 2015 Tianjin blasts as a case study, this article investigates China Global Television Network (CGTN) and CNN International’s coverage of the disaster. The empirical study finds that despite their overlapping news values,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Chinese and Russian external communication styles are in part directly reflected by CGTN and RT. Empirical studies have suggested that CGTN tends to adopt official sources (Fearon and Rodrigues 2019;Gabore 2020) and have confirmed Yang's (2017, 86) observation that CGTN vows to "push Chinese perspectives and voices into the international arena in order to contest the discursive power of the West." Moreover, increasing evidence indicates that CGTN is employing a new strategy of "borrowing mouths," which refers to the use of pro-China sources to legitimize the Chinese policy line (Alpermann 2020).…”
Section: Chinese and Russian International Broadcasting During Times ...mentioning
confidence: 75%
See 3 more Smart Citations
“…Chinese and Russian external communication styles are in part directly reflected by CGTN and RT. Empirical studies have suggested that CGTN tends to adopt official sources (Fearon and Rodrigues 2019;Gabore 2020) and have confirmed Yang's (2017, 86) observation that CGTN vows to "push Chinese perspectives and voices into the international arena in order to contest the discursive power of the West." Moreover, increasing evidence indicates that CGTN is employing a new strategy of "borrowing mouths," which refers to the use of pro-China sources to legitimize the Chinese policy line (Alpermann 2020).…”
Section: Chinese and Russian International Broadcasting During Times ...mentioning
confidence: 75%
“…This echoes an interview with CGTN's controller Liu Cong, in which he states that CGTN not only envisions to empower "a variety of voices … not just voice of China but also voices of other Asian countries, of African countries and of Latin American nations" (Li and Wu 2018, 41). Although previous studies have attributed CGTN's sourcing patterns, such as prioritizing official sources, to Confucian culture (Fearon and Rodrigues 2019) and attributed the vocalization of developing countries to China's strategy of maintaining diplomatic relationships (Gabore 2020), we consider these strategies to be the implementation of China's developing country identity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Deklaratīvie runas akti saistās ar realitātes fiksāciju juridiskā formātā. 43 Tie var pārklāties ar citiem runas aktiem funkcionalitātē, taču, Sīrla skatījumā, noteikti ir nepieciešami nobriedušā un stabilā noteikumu vidē kā likuma gara fiksējošais elements dažādos attiecību regulējumos. Sadarbības memorandi, nolīgumi, vienošanās un līdzvērtīgi fiksēti runas akti, kaut arī deklaratīvi (kā liecina to tipoloģiskais nosaukums), vienlaikus ar savu kvantitāti liecina par noteikumu sistēmas stabilitāti, jo deklaratīvie runas akti principā stiprina pastāvošās noteikumu struktūras.…”
Section: Sociālā Konstruktīvisma Teorētiskās Nostādnes Un Kognitīvās ...unclassified